2021
DOI: 10.1177/09746862211007035
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Characteristics,Corporate Social Responsibility, Resource Productivity And Firm Performance: An Empirical Study

Abstract: Corporate governance continues to be at the forefront as evinced by some of the recent incidents at organisations such as Tata Sons, Yes Bank and ICICI bank. Traditionally, ownership characteristics have been considered as close substitutes representing corporate governance, considering that board processes and activity do not yield themselves to much scrutiny beyond a few media reports and analysis. The research article undertakes a study of ownership, corporate social responsibility(CSR) and resource product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…They also report that companies that are open to institutional investors and have more board members tend to demonstrate a superior reputation. Similarly, Prince (2021) also reports that the ownership variables significantly positively influences a company’s reputation. Ajay and Madhumathi (2015) have reported that Indian companies having higher INS tend to have better earnings quality thus constraining the management from misusing their powers to misrepresent the company’s earnings.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 95%
“…They also report that companies that are open to institutional investors and have more board members tend to demonstrate a superior reputation. Similarly, Prince (2021) also reports that the ownership variables significantly positively influences a company’s reputation. Ajay and Madhumathi (2015) have reported that Indian companies having higher INS tend to have better earnings quality thus constraining the management from misusing their powers to misrepresent the company’s earnings.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 95%
“…Literature on CSR and competitiveness suggests the need for studying various types of resources, their allocation and productivity related to firms' CSR activities in the Asian context (Battisti et al, 2022). In the Asian developing country context, a handful of studies Figure 7 CSR-led competitiveness resources generation have looked at the challenges and outcomes of resource mobilization for CSR activities (Khan et al, 2019;Nair and Som Sekhar, 2019;Prince, 2021;Le, 2022). Studies have also looked at the impact of country-specific regulatory changes (for example, India's mandatory CSR laws) on the resource allocation, productivity and competitiveness of firms doing CSR in the country (Nair and Som Sekhar, 2019;Prince, 2021).…”
Section: Cluster 2: Corporate Social Responsibility-led Competitivene...mentioning
confidence: 99%
“…In the Asian developing country context, a handful of studies Figure 7 CSR-led competitiveness resources generation have looked at the challenges and outcomes of resource mobilization for CSR activities (Khan et al, 2019;Nair and Som Sekhar, 2019;Prince, 2021;Le, 2022). Studies have also looked at the impact of country-specific regulatory changes (for example, India's mandatory CSR laws) on the resource allocation, productivity and competitiveness of firms doing CSR in the country (Nair and Som Sekhar, 2019;Prince, 2021). Such studies find that firm's face unique challenges in orchestrating resource-based strategies for CSR-led competitiveness in Asian contexts, and more research is required to detail these nuances (Nair and Som Sekhar, 2019;Battisti et al, 2022).…”
Section: Cluster 2: Corporate Social Responsibility-led Competitivene...mentioning
confidence: 99%